2012
DOI: 10.1002/anie.201206558
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Bases as Useful Probes of Lithium Amide Reactivity

Abstract: Lithium amides are indispensable as strong bases in organic synthesis, particularly for the generation of metal enolates from compounds that possess C = O functions of all types. [1] These reagents exhibit complex structural behavior, particularly in solution, in which the formation of aggregates and mixed aggregates is commonplace, leading to a mechanistically rich repertoire of enolization and metalation chemistry. [2] Our own interest in this area has focused on the use of chiral lithium amides in asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The enantiopure amine (R)-1-phenylethyl-2,2,2-trifluoroethylamine was first prepared by Koga, 26 and the corresponding chiral lithium amide has also been studied in some depth by Simpkins. 27 In this work, reaction of LiN(R-CH(Ph)-Me)(CH 2 CF 3 ) with CuMes in toluene gave a solution from which crystals of the organoamidocuprate [Cu 2 Li 2 Mes 2 (N(R-CH(Ph)Me)(CH 2 CF 3 )) 2 ] (4) were obtained. X-ray diffraction studies (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The enantiopure amine (R)-1-phenylethyl-2,2,2-trifluoroethylamine was first prepared by Koga, 26 and the corresponding chiral lithium amide has also been studied in some depth by Simpkins. 27 In this work, reaction of LiN(R-CH(Ph)-Me)(CH 2 CF 3 ) with CuMes in toluene gave a solution from which crystals of the organoamidocuprate [Cu 2 Li 2 Mes 2 (N(R-CH(Ph)Me)(CH 2 CF 3 )) 2 ] (4) were obtained. X-ray diffraction studies (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Initial experiments employing chiral bases in the desymmetrizing aldol addition showed promising enantioselectivity (37% ee, see Supporting Information) in the formation of 21 , demonstrating proof-of-principle for an enantioselective synthesis of 1 in the event that the sulfation problem can be solved. [29] In the course of this endeavour, we demonstrated that our computation-based hypothesis about the configurational preferences of the C2 hemiaminal were correct. Finally, given the presumed biosynthetic relationship with the halenaquinol family of natural products, we extend the possibility that the compound that we have made, exiguaquinol dessulfate, could be an as-yet-uncovered natural product.…”
mentioning
confidence: 83%
“…Preliminary studies towards applying the newly available C 2 -symmetric secondary amines in asymmetric synthesis,i n which they were used as alithium amide base in abenchmark enol silane synthesis,a nd as part of an ew phosphoramidite ligand for use in the asymmetric addition of arylboron reagents to acyclice nones, [15] confirmed their promise.B oth reactions investigated gave results comparable to analogous known transformations. [16] We currently envision acatalytic cycle that is initiated by the protonation of imine 1aby chiral DSI-2f(Scheme 1). The resulting iminium ion pair A undergoes reaction with Hantzsch dihydropyridine 3 to give enantiomerically enriched primary amine salt B and the corresponding Hantzsch pyridine.S ubsequently,a mine B undergoes at ransimination with substrate 1a,f irst to produce aminal C,w hich then liberates ammonia to form the secondary iminium ion pair D. [17] Finally,asecond reduction of intermediate D provides diastereo-and enantioenriched secondary amine product 5a.…”
mentioning
confidence: 99%